An assessment of the integration of the community resource management framework in the comprehensive land use plan the case of Nalundan United Farmers Association, Inc. of barangay Nalundan, Bindoy, Negros Oriental. - Gibe, Rogelio C.
The Local Government Code (LGC) of 1991 brought significant improvements in natural resource management from centralized to decentralized governance. However, local government units (LGUs) have yet to fully reap the benefits of the LGC. Further, the national government adopts Community-Based Forest Management (CBFM) as the country's strategy to promote sustainable forest management, where the local community, represented by the people's organization (PO) and serving as forest managers, enters into a CBFM agreement to manage specific portions of forestlands by the approved Community Resource Management Framework (CRMF) with four components: forest development, organizational development, livelihood/ enterprise development, and support services. The latter two components are beyond the mandate of the DENR; however, the PO tends to depend solely on the DENR. This, in turn, leads to the failure to achieve the stated goal and vison, which are intended to promote sustainable development within the community. Integrating the CRMF into the comprehensive land use plan (CLUP) allows the LGUs to effectively address components that are beyond the mandate of the DENR. Therefore, this study explored how the development needs of the upland communities, particularly the holders of the CBFM Agreement through the CRMF, can be integrated into the CLUP in consideration of the components of the local planning system, using the case of Nalundan Upland Farmers Association, Inc. (NUFAI) and the Municipality of Bindoy, Negros Oriental. This study focused on the ways in which the CRMF could be integrated into the CLUP to contribute towards ensuring sustainable development in the CBFM community and may transcend to the whole municipality. It considered the four components of local planning systems as entry points for integration, particularly the planning structure, planning process, plan content, and plan implementation. The study employed qualitative research through descriptive and content analysis and used the triangulation method through key informant interviews, focus group discussions, document review, and actual observations in the community. The study found that the CRMF of NUFAI and the CLUP of the Municipality of Bindoy are not integrated. This is due to the factors identified, such as the unclear roles and responsibilities of LGUs in the integration process, limited participation and understanding of both plans among stakeholders, neglect of crucial activities such as scanning of plans, and non-participation of CBFM-POs in the CLUP process, timing misalignment and format differences, differences in implementation mechanisms, funding issues, and lack of attention to land use planning, which hinder effective integration and implementation. The results further revealed opportunities to integrate the CRMF into the CLUP across various planning components. Both CRMF and CLUP guidelines acknowledge the importance of LGU, CBFM-POs, and DENR representation in planning teams, but implementation requires clarifying LGU roles and specifying which LGU office should be involved in the CRMF Facilitators Team. To ensure integration, LGUs should involve CBFM-POs in the CLUP while providing training for LGUs in CRMF, and CBFM-POs and DENR personnel in the CLUP are recommended. Challenges in integrating forms and templates may arise, but alignment in plan content is feasible, with the CLUP providing general land uses and the CRMF offering detailed information. However, there is currently no integration in implementation mechanisms, as CRMF lacks a mechanism similar to the CLUP's zoning ordinance.